Pengaruh Gaya Kepemimpinan Demokratis, Komitmen Afektif dan Disiplin Kerja terhadap Kinerja pada Dinas Kesehatan Kota Yogyakarta - Arfid Wona Awang, John Gilbert; Prayekti; Selamer Hartanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of Democratic Leadership Style (X1), Affective Commitment (X2), and Work Discipline (X3) on Performance (Y). This research uses quantitative descriptive research, because the data in this research is in the form of numbers and analysis uses statistics. Quantitative descriptive research is a series of research that requires a lot of use of numbers. These data were obtained from questionnaires announced to respondents. The population in this research were employees at the Kantor Dinas Kesehatan Kota Yogyakarta by taking a sample of 53 people. Then the data obtained from the distribution of questionnaires was processed using SPSS version 25 by carrying out data quality tests, classical assumption tests, t tests and coefficient of determination. The results of significance testing show that the democratic leadership style variable (X1) has a value of tcount = 2.234 > rtable = 1.6741 with a significance value of 0.030 < 0.05, the affective commitment variable (X2) has a value of tcount = 10.609 > rtable = 1.6741 with a significance value of 0.000 < 0.05, and the Work Discipline variable (X3) has a tcount = 5.138 > rtable = 1.6741 with a significance value of 0.000 < 0.05. Based on the test results in this research, it shows that the variables Democratic Leadership Style, Affective Commitment, and Work Discipline individually or partially have a positive and significant influence on the employee performance variable at the Kantor Dinas Kesehatan Kota Yogyakarta.